LAYANAN KONSELING MENGGUNAKAN METODE SOSIODRAMA - MUHAMMAD HUSAINI; SYUKERI GAZALI (STIT DARUL ULUM KOTABARU, 2024)
resolving their issues. Counselors often encounter students facing challenges in learning and motivation due to conflicts. There are many factors that cause conflicts to arise, whether internal (within the individual), interpersonal conflicts, group conflicts, or intergroup conflicts (external). Understanding these factors helps counselors/guidance teachers address and resolve conflicts, channeling them towards positive development. Conflict among students at the junior high school (SMP/MTs) level is a common issue related to their developmental characteristics as early adolescents. This study seeks to address student conflict issues using the Sociodrama method, as it can address social problems, including conflicts among students. This research is a classroom action research, involving close examination of learning activities through a deliberately implemented action, occurring within a classroom setting. Based on the study results, there is an increase in students' understanding of conflict resolution within groups. Initially, students frequently encountered conflict-related problems, but with the use of the Sociodrama method, they gained insights into conflict resolution. Although the first cycle was not fully effective due to certain limitations regarding the teacher, students, media, Sociodrama script, and situational factors, improvements were made in the second cycle based on feedback from evaluations and reflections conducted with collaborators. These adjustments resulted in a significant improvement in students' understanding in the second cycle.